Risk Factors of Occipital Stroke in Tertiary Eye Center in Yogyakarta, Indonesia: Oral Presentation - Observational Study - Resident - BUDHI HARTIWI SATYAWATI; INDRA TRI MAHAYANA; HARTONO (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Occipital stroke is a stroke involving occipital lobe of the brain which can impair the visual acuity in patient. Several risk factors have been identified as a predisposing conditions. Objectives The aim of this study is to investigate the risk factors for occipital stroke. Methods : It is a cross sectional research by analyzing secondary data from medical record of patients with occipital stroke hospitalized in Dr. Yap Eye Hospital in Yogyakarta from January 2021 to December 2022 were included in this study. Demographyy, clinical data, and risk factors associated with occipital stroke was recorded. The descriptive statistic was performed to evaluate risk factors for occipital stroke. Results : Subjects were analyzed 61, comprised of 44 males (72%) and 17 females (28%). Majority of subjects age ≥45 years old (93%). Attack occurred during activity (n=54, 89%), during wake up (n=7, 11%). The involvement right eye (n=8, 13%), left eye (n=9, 15%), & bilateral (n=44, 72%). From 122 eyes, 74 hemianopia (61%), 34 quadranopia (28%) and 14 bilateral hemianopia (11%). 29 subjects had right occipital stroke (48%), 25 subjects hadleft occipital stroke (41%) and 7 subjects had bilateral occipital stroke (11%). Most subjects had one risk factor (n=29, 48%) and two risk factors (n=23, 38%). Eight subjects had three risk factor (13%) and only one subject had four risk factors (2%). Conclusion : The majority of risk factors of occipital stroke involved only single risk factors and double risk factors. Only minority of subjects had multiple risk factors.